Prucalopride in diabetic and connective tissue disease‐related gastroparesis: Randomized placebo‐controlled crossover pilot trial. Issue 1 (2nd August 2020) - Andrews, Christopher N.; Woo, Matthew; Buresi, Michelle; Curley, Michael; Gupta, Milli; Tack, Jan; Wilsack, Lynn; Nasser, Yasmin
Abstract: Background: Gastroparesis, defined by delayed gastric emptying in the absence of mechanical outlet obstruction, is a frequent neuropathic complication of diabetes mellitus, and effective treatments are lacking. Prucalopride is a pan‐gut prokinetic with selective agonist effects on serotonin 5‐HT4 receptors in the gut. This study aimed to assess the effect of prucalopride 4 mg daily on Gastroparesis Cardinal Symptom Index (GCSI), meal‐related symptom score (MRSS), and gastric emptying rate in diabetic or connective tissue disease (CTD)‐related gastroparesis patients. Methods: This was a double‐blind crossover trial of four‐week treatment periods with prucalopride or placebo divided by two weeks of washout. GSCI, MRSS, gastric emptying scintigraphy, PAGI‐SYM, and PAGI‐QoL were assessed at baseline and the end of each treatment period. Daily bowel movement (BM) frequency and gastrointestinal symptoms were recorded in each period. Key Results: Fifteen gastroparesis patients (13 diabetic, 2 CTD) were enrolled. GCSI scores were lower than baseline but not different between treatment arms. MRSS scores over time or cumulative score were not significantly different between groups. Gastric emptying was more rapid in the prucalopride treatment period, with mean four‐hour meal retention of 22 ± 6% in PRU period vs 40 ± 9% in the placebo period ( P  = 0.05). Weekly BM frequency was significantly higher in prucalopride than placebo periods (10.5 ± 1.8 vs 7.5 ± 0.8, P  < 0.0001). Perception of weight loss was higher in patients on prucalopride. Analysis of diabetic gastroparesis (n = 13) population did not change the conclusions. Conclusion and Inference: Prucalopride at 4 mg accelerates gastric emptying and bowel movement frequency but does not appear to ameliorate gastroparesis or meal‐related symptoms in this study. Abstract : This study recruited 15 patients with gastroparesis (13 diabetic) who were given prucalopride 4 mg daily or placebo for 4 weeks in a randomized, double‐blind, placebo‐controlled crossover design. The primary outcome measures of symptoms were not different between groups. However, gastric emptying and bowel movement frequency were accelerated with prucalopride. The medication was well tolerated. Further study with larger sample sizes, and/or dose adjustment, is warranted.